(untitled) (International Journal of Food and Nutritional Sciences, 2019)
As the film industry transcends geographical boundaries and embraces diverse narratives, understanding the global dimensions of storytelling becomes paramount. Through a comprehensive analysis of films spanning different cultures, this study seeks to identify recurring themes, narrative structures, and visual styles that contribute to the rich mosaic of global cinema. By examining the ways in which filmmakers represent and interpret various cultures, the research sheds light on the interconnectedness of storytelling traditions on a global scale. The findings not only enhance our comprehension of cinematic diversity but also underscore the potential of film as a powerful medium for fostering cross-cultural dialogue and appreciation. This investigation ultimately contributes to the broader discourse on the universal language of cinema and its role in shaping our collective understanding of the human experience. In an era marked by the unprecedented globalization of the film industry, the study employs a comprehensive and nuanced approach to investigate how filmmakers, hailing from varied corners of the globe, articulate and represent distinctive cultural narratives on the cinematic canvas.